Evaluation of the effects of COVID-19 pandemic on sleep habits and quality of life in children (Annals of Medical Research, 2021)
Aim: Children are thought to be one of the groups most affected by the psychosocial impact of the pandemic. The aim of this study is to examine the effects of COVID-19 pandemic on sleep habits and quality of life in children.Materials and Methods: 60 children between the ages of 8-13, who were not diagnosed with any psychiatric disorder with regard to pre-pandemic period according clinical assessment and “Kiddie Schedule for Affective Disorders and Schizophrenia for School-Age Children- Present and Lifetime Version (KSADS-PL)” semi-structured interview tool, clinically normal intelligence level, did not have any medical illness that required treatment, had no history of adverse life events other than Covid pandemic, and had verbal consent and written informed consent of the family were included. Pre-pandemic and pandemic data were evaluated with Children's Sleep Habits Questionnaire (CSHQ)- Short Form, Pediatric Quality of Life Inventory (PesdQL) parent forms and Screen for Child Anxiety Related Disorders (SCARED), Children's Depression Inventory (CDI) self-report scales.Results: “Bedtime resistance”, “Delayed sleep onset”, “Night awakenings”, “Parasomnias”, “Daytime sleepiness” scale scores increased statistically significantly during the pandemic period. A statistically significant decrease was also found in all PedsQL scale scores compared to the pre-pandemic period. All CSHQ subscales except "sleep duration" related to the pandemic period were found to be statistically correlated with PedsQL scale scores. Additionally, statistically significant increases were found in SCARED anxiety and CDI depression scores of children during the pandemic period compared to the pre-pandemic period. Furthermore, anxiety and depression scores were found to be correlated with both sleep problems and decrease in psychosocial quality of life domains except social anxiety.Conclusion: The results of our study indicate that COVID-19 pandemic may affect sleep habits and quality of life of children. We suggest that interventions targeted to regulate sleep habits are important for well-being of children during and after the pandemic. In addition, the results of increased anxiety and depression levels and the correlations between anxiety, depression with sleep problems and worse quality of life indicates the importance of evaluating anxiety and depression among children during COVID-19 pandemic.